Remote Chemistry Labs: Academic Success and Opinions of First-Year Science Students Using PDEODE Model - Özbulut, Nehir; Uyulgan, Melis Arzu (Jurnal Penelitian dan Pembelajaran IPA, 2024)
The PDEODE (Prediction-Discussion-Explanation-Observation-Discussion-Explanation) instructional model, with its structured approach that fosters prediction, discussion, explanation, observation, and subsequent discussions, stands out as a powerful tool for enhancing students’ scientific thinking skills and engagement in the scientific process. Research on the implementation and effectiveness of the PDEODE strategy is essential for comprehending its impact on student learning outcomes, conceptual understanding, critical thinking abilities, and social skills within the context of laboratory education. In this paper, we investigated the implementation of the PDEODE in science education within remote learning processes and examined its impact on students’ academic success. The results showed a positive improvement in students’ academic success over a 6-week period when PDEODE was integrated into laboratory experiments. The model’s effectiveness in enhancing students' scientific understanding and thinking was evident through their active participation and discussions. Furthermore, positive feedback from students regarding the model’s effectiveness in remote learning environments, as well as their perceptions of improved understanding and enjoyment, further emphasizes the significance of the PDEODE approach in enhancing learning outcomes. This paper suggests that further exploration of the integration of the PDEODE model in various science courses and learning settings could greatly enhance educational experiences.